2022
DOI: 10.21511/kpm.06(1).2022.08
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy exchange and its challenges in Post-Soviet Georgia

Abstract: Financial literacy is becoming an urgent challenge in many countries. This situation is more acute in a developing country with a Soviet experience. The affected population, who are in advanced positions in the international financial machinations of the current period, is unmistakable proof of the low level of financial awareness in Georgia. The present study aims to determine the impact of student financial literacy on consumer behavior in Georgia as a Post-Soviet country. The study uses statistical methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Scientific studies are devoted to the role of financial education as a need for adults. Surmanidze et al (2022) note that a relatively low level of financial literacy was indicated; students do not understand that they need to increase their financial education and skills, which makes the current situation even more dramatic. Bibliometric analysis on the subject of the relationship between adult education and economic indicators was carried out also by Koibichuk et al (2022) and Strielkowski et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scientific studies are devoted to the role of financial education as a need for adults. Surmanidze et al (2022) note that a relatively low level of financial literacy was indicated; students do not understand that they need to increase their financial education and skills, which makes the current situation even more dramatic. Bibliometric analysis on the subject of the relationship between adult education and economic indicators was carried out also by Koibichuk et al (2022) and Strielkowski et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%